DIE EIGNUNG DER INTERNETSEITE de.islcollective.com ALS LEHRSCHREIBMATERIALLIEN DEUTSCHER SPRACHE IN SMK NEGERI 1 BOYOLANGU - SLAMET, NUR (LATERNE, 2013)
One internet site commonly used in the German language learning website de.islcollective.com. De.islcollective.com site is a site that contains writing exercises that vary. The exercises are also presented in this site is interesting, which is expected to attract students to deepen German language. The research problem addressed in this study were (1) How the suitability of the material on the site de.islcollective.com the curriculum at SMK Negeri 1 Boyolangu?. (2) How does the use of the site as a learning material de.islcollective.com write German language in SMK Negeri 1 Boyolangu?. While the purpose of this study was (1) to describe the suitability of the material on the site de.islcollective.com the curriculum at SMK Negeri 1 Boyolangu. (2) To describe the use of the site as a learning material de.islcollective.com write German language in SMK Negeri 1 Boyolangu. This research is a descriptive qualitative research which is then analyzed and described. The results of this study are: (1) writing material taken at the site in accordance with the map description de.islcollective.com material contained in SMK Negeri 1 Boyolangu. It is demonstrated the relevance between the types of exercises with the Competence Standard and Basic Competence in the curriculum contained in SMK Negeri 1 Boyolangu. (2) Use of the site de.islcollective.com in SMK Negeri 1 Boyolangu very attractive and effective for students as learning materials written German language, because the training given to the students, presented in an interesting and use language that is very light and simple. So that students are easier to understand and students can directly apply them in real life. From these results, we recommend that teachers use de.islcollective.com site, so as to assist in the learning process of innovative and fun for students Keywords: de.islcollective.com websites, writing skills